Current Evidence for Postoperative Monitoring of Microvascular Free Flaps: A Systematic Review. Issue 5 (May 2015) - Chae, Michael P.; Rozen, Warren Matthew; Whitaker, Iain S.; Chubb, Daniel; Grinsell, Damien; Ashton, Mark W.; Hunter-Smith, David J.; Lineaweaver, William C.
Abstract : Background: Despite a plethora of monitoring techniques reported in the literature, only a small number of studies directly address clinical relevant end points, such as the flap salvage rate and false-positive rate. Method: We conducted a systematic review of current evidence regarding the postoperative monitoring of microvascular free-tissue transfer via extensive electronic and manual search and perusing databases, such as PubMed, Cochrane, American College of Physicians (ACP) Journal Club, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Excerpta Medica Database (EMBASE), and Ovid MEDLINE. The included literature (n = 184 publications) was critically appraised using March 2009 Oxford Centre for Evidence-Based Medicine definitions, focusing on the evidence for the efficacy of each technique in improving the flap salvage rate of compromised flaps. Result: There is a paucity of outcome-based studies, with only implanted Doppler probes, near-infrared spectroscopy, laser Doppler flowmetry, quantitative fluorimetry, and digital photography assessment using smartphones having been demonstrated in comparative studies to improve flap salvage rate. Currently, the implantable Doppler probe is the technique with the largest number of comparative studies and case series to demonstrate its effectiveness compared with clinical monitoring. Conclusions: Future studies need to evaluate the most promising monitoring techniques further with a focus on assessing clinically relevant outcomes, such as the flap salvage rate and the false-positive rate, and not simple clinical series reporting patient and physician satisfaction.